Lung endothelium exploits susceptible tumor cell states to instruct metastatic latency - Jakab, Moritz; Lee, Ki Hong; Uvarovskii, Alexey; Ovchinnikova, Svetlana; Kulkarni, Shubhada; Jakab, Sevinç; Rostalski, Till; Spegg, Carleen; Anders, Simon; Augustin, Hellmut (Nature cancer, 2024)
In metastasis, cancer cells travel around the circulation to colonize distant sites. Due to the rarity of these events, the immediate fates of metastasizing tumor cells (mTCs) are poorly understood while the role of the endothelium as a dissemination interface remains elusive. Using a newly developed combinatorial mTC enrichment approach, we provide a transcriptional blueprint of the early colonization process. Following their arrest at the metastatic site, mTCs were found to either proliferate intravascularly or extravasate, thereby establishing metastatic latency. Endothelial-derived angiocrine Wnt factors drive this bifurcation, instructing mTCs to follow the extravasation-latency route. Surprisingly, mTC responsiveness towards niche-derived Wnt was established at the epigenetic level, which predetermined tumor cell behavior. Whereas hypomethylation enabled high Wnt activity leading to metastatic latency, methylated mTCs exhibited low activity and proliferated intravascularly. Collectively the data identify the predetermined methylation status of disseminated tumor cells as a key regulator of mTC behavior in the metastatic niche.
Gesehen am 27.02.2024